Oil palm (Elaeis guineensis Jacq.) frond feeding of goats in the humid tropics - Ebrahimi, Mahdi; Rajion, Mohamed Ali; Goh, Yong Meng; Sazili, Awis Qurni; Soleimani, A. F.; Schonewille, Jan Thomas (Medwell Journals, 2013)
Twenty four goats were allocated to three groups (n = 8) and fed either a control diet Without Oil Palm Fronds (CON), a diet incorporated with 25% Oil Palm Fronds (OPFM) or 50% Oil Palm Fronds (OPFH) for 100 days to evaluate their growth rates, carcass characteristics and subcutaneous fatty acid profiles. Animals in all three groups exhibited similar final body weights (p>0.05). The OPFH group showed a significant linear reduction (p<0.05) in dressing percentage, warm carcass weight and back fat thickness and total muscle when compared to the CON group. The total n-3 Polyunsaturated Fatty Acid (PUFA) concentrations in the subcutaneous fat of the OPFH animals were significantly higher (linear, p<0.05) than the CON group. The diet containing 25% of oil palm fronds did not produce any adverse effects on the growth performance and carcass characteristics. This demonstrates an environmental-friendly way of utilizing agricultural waste by products for the small ruminant industry in tropical countries growing oil palm tree.